Pengembangan Ekstrakurikuler ROHIS (Rohani Islam) dalam Pembinaan Karakter Religius Peserta Didik - Fauzi, Imron; Firman, Firman (MANAGIERE: Journal of Islamic Educational Management, 2023)
Extracurriculars are supporting activities carried out by students. Rohis (Rohani Islam) is an Islamic-based forum. Religious character is coaching in the character education of students. The religious activities carried out in Rohis activities can increase faith and devotion to God Almighty, and familiarize students with noble character and develop better attitudes, as well as increasing extensive religious knowledge. This research uses a descriptive qualitative approach. This research subject was taken using purposive techniques and data collection techniques using observation, interviews and documentation. The data analysis used is the Miles and Huberman model data analysis, which uses 3 stages in its implementation, namely data reduction, data display, and conclusion drawing/verification. Validity of data using triangulation of methods and sources. The research results obtained are: 1) The activity of reciting the Koran can develop broad religious knowledge. 2) Dhuha prayer activities can develop discipline, revive religious breath, and be obedient to worship. 3) The activity of reading verses from the Holy Qur'an can provide positive energy, calm the soul and love peace, and create an environment of character that embodies Islam. 4) Pilgrimage activities include awareness of death and the next life in the afterlife, taking lessons from the story of one's life.